12(2j-6)=0

Simple and best practice solution for 12(2j-6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(2j-6)=0 equation:


Simplifying
12(2j + -6) = 0

Reorder the terms:
12(-6 + 2j) = 0
(-6 * 12 + 2j * 12) = 0
(-72 + 24j) = 0

Solving
-72 + 24j = 0

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '72' to each side of the equation.
-72 + 72 + 24j = 0 + 72

Combine like terms: -72 + 72 = 0
0 + 24j = 0 + 72
24j = 0 + 72

Combine like terms: 0 + 72 = 72
24j = 72

Divide each side by '24'.
j = 3

Simplifying
j = 3

See similar equations:

| 3v=9.6 | | -21=7v | | 92=x/4 | | (1+u)(5u-6)=0 | | 12-6y-1= | | f(x)=(1.5)x | | 1.25(2c-1)=3c-2 | | 3b+1=28 | | 0.06(a+200)+0.01a=172 | | x/9-9=8 | | 3(x+5)+4(x-3)+-6x=4 | | (8x^2-7x+2)+(3x^2-9x-6)= | | 2(x-4)+x-y=2y-9 | | -8(x-7)-9=47 | | 2(s+6)+2(s-1)+-4=74 | | (5z-9)(8+z)=0 | | x/3=4x/21-7 | | 60x-50=15x-5 | | x/3=4x/21 | | 13-4y+1y= | | 3(m+3)+5(m+1)+-6m=50 | | m=40 | | 6x+3(-3x-7)=0 | | 5x+15=x-20 | | 9xsquared-21=0 | | X-6-x-4=10-c | | -104=5x-3(5x+8) | | .5f=c+6u | | -3+5(b+4)+4(b+3)=2 | | x^(-3/5)=27 | | -7x-6(2x+5)=84 | | 3(n+3)+-2n+2(n+4)=65 |

Equations solver categories